Small vessel disease is linked to disrupted structural network covariance in Alzheimer's disease. Issue 7 (27th January 2017) - Nestor, Sean M.; Mišić, Bratislav; Ramirez, Joel; Zhao, Jiali; Graham, Simon J.; Verhoeff, Nicolaas P.L.G.; Stuss, Donald T.; Masellis, Mario; Black, Sandra E.
Abstract: Introduction: Cerebral small vessel disease (SVD) is thought to contribute to Alzheimer's disease (AD) through abnormalities in white matter networks. Gray matter (GM) hub covariance networks share only partial overlap with white matter connectivity, and their relationship with SVD has not been examined in AD. Methods: We developed a multivariate analytical pipeline to elucidate the cortical GM thickness systems that covary with major network hubs and assessed whether SVD and neurodegenerative pathologic markers were associated with attenuated covariance network integrity in mild AD and normal elderly control subjects. Results: SVD burden was associated with reduced posterior cingulate corticocortical GM network integrity and subneocorticocortical hub network integrity in AD. Discussion: These findings provide evidence that SVD is linked to the selective disruption of cortical hub GM networks in AD brains and point to the need to consider GM hub covariance networks when assessing network disruption in mixed disease.